2021
DOI: 10.1016/j.radcr.2021.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Partial splenic embolization treats recurrent left pleural effusions in a patient with portal venous system thrombosis

Abstract: A 56-year-old female with thrombocythemia complicated by portal venous system thrombosis presented with recurrent left pleural effusions after failed recanalization via mechanical thrombectomy and stenting at an outside center. With no other cause, splenic vein thrombosis and left-sided portal hypertension was suggested as a possible etiology. Partial splenic embolization was performed with immediate decrease in effusions and resolution by 8 weeks. Portal and splenic venous system thrombosis may cause recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our patient refused any invasive management after the initial thoracentesis and opted for conservative management. While no strong evidence exists to guide management in these cases, splenectomy and partial splenic embolization have been described for recurrent pleural effusion seen with splenomegaly of varying etiologies [2,12,13]. The pleural effusion in our patient almost entirely resolved spontaneously after the initial recurrence, suggesting physicians can consider watchful monitoring in these cases after discussing with the patient.…”
Section: Discussionmentioning
confidence: 68%
“…Our patient refused any invasive management after the initial thoracentesis and opted for conservative management. While no strong evidence exists to guide management in these cases, splenectomy and partial splenic embolization have been described for recurrent pleural effusion seen with splenomegaly of varying etiologies [2,12,13]. The pleural effusion in our patient almost entirely resolved spontaneously after the initial recurrence, suggesting physicians can consider watchful monitoring in these cases after discussing with the patient.…”
Section: Discussionmentioning
confidence: 68%
“…The microsphere with the size of 300-500 um can reach the distal end of the blood vessel and achieve the terminal embolization, which is not easy to form collateral circulation and reduce the recurrence of hypersplenism. The common side effects and complications of partial splenic embolization include post embolization syndrome (such as abdominal pain, fever, vomiting), portal vein thrombosis, liver failure, pleural effusion, ascites and splenic abscess [38,[50][51][52][53]. Gabriele Piffaretti et al [54] reported that postembolization syndrome is common and has been reported as 30% but generally resolving without sequelae.…”
Section: Discussionmentioning
confidence: 99%